Pengembangan Kelembagaan dan Pembiayaan Geopark di Indonesia: Tantangan dan Strategi: Geopark Institutional Development and Financing in Indonesia: Challenges and Strategies - Forina Lestari; Ira Indrayati (P4W LPPM IPB, 2022)
Geopark development is one of the national priority programs currently being intensified by the government at both the central and regional levels. There are three pillars of geopark development, namely conservation, economy (tourism), and education, that form the basis for sustainable regional development. This research focuses on institutional development and financing with case studies in Indonesia. Methods used in this research include literature study, online surveys to the Geopark Management Agency in Indonesia, and focus group discussions with experts and the central and regional governments. A content analysis was carried out with a descriptive approach to formulate alternative strategies for institutional development and financing in Indonesia. Results of this research show that institutions are the key to achieving independent, professional, and sustainable governance. In terms of financing, the Geopark management agency needs to be proactive in increasing alternative sources of financing such as innovation in geoproducts and geoservices, opportunities for collaboration with the private sector and the community, grant and loan, geo-sites assets management and others.